Nonlinear unsteady MHD flow in an inclined channel with suction and heat generation: time periodic boundary conditions (Journal of Naval Architecture and Marine Engineering, 2025)
This paper is presented to analyze the task of assimilating parameters on MHD flow structure in a sloped pipeline while certain plate is disorderly heated. The impact of suction and heat generation is considered. The dictating liquid motion and energy equations are ascertained and corresponding expressions for thermal energy, liquid motion, fanning friction and stress flatten are acquired. In particular, the liquid motion behaves an increasing function of suction parameter and a decreasing function of magnetic parameter. This research is of special consequence in marine steam engineering, naval ships mooring and replenishment, medicine, and aerodynamics. Results are verified in special case with those existing in the literatureJournal of Naval Architecture and Marine Engineering, 22(2), 2025, PP. 199-216